KORELASI DAYA LEDAK TUNGKAI DAN KESEIMBANGAN TERHADAP KETERAMPILAN MENENDANG BOLA KE GAWANG PADA PERMAINAN SEPAKBOLA CLUB MATAHARI FC GOWA - M. Adam Mappaompo; Ians Aprilio; Poppy Elisano Arfanda (KORSA: Jurnal Kajian Ilmu Keolahragaan dan Kesehatan, 2023)
The results of this research show a correlation between leg explosive power and the skill of kicking the ball into the goal of Club Matahari Fc Gowa with an r value of 0.698. And the correlation between balance and the skill of kicking the ball into the goal of Club Matahari Fc Gowa. The r value is 0.668 and the correlation between leg explosive power and balance on the skill of kicking the ball into the goal of Club Matahari Fc Gowa. The R value is 0.803